Rice residue management alternatives and nitrogen optimization: impact on wheat productivity, microbial dynamics, and enzymatic activities - Chaudhary, Charul; Yadav, Dharam B.; Hooda, Virender S.; Chaudhary, Ankur; Parshad, Jagdish; Kumar, Ankush; Khedwal, Rajbir SIngh; Yadav, Ashok (Frontiers in Sustainable Food Systems, 2024)
The research is related to rice-wheat cropping system which constitutes a dominant agricultural paradigm in South-eastern Asia.Recent estimates indicate that Southeast Asian countries collectively generate 150 million metric tons of rice residue annually. On average, paddy cultivation yields approximately 5-6 tonnes of straw per hectare. This cropping system holds paramount importance for the sustenance of livelihoods, food security, employment, and income generation. The window between paddy harvesting and sowing of wheat, is typically spanning 2-3 weeks, compelling farmers to resort to paddy straw burning. Also, the ricewheat cropping system confronts numerous secondary challenges, including declining groundwater tables, deteriorating soil health, and diminished total factor productivity. Crop residues serve as a nutrient-rich source, liberating essential plant nutrients upon microbial decomposition in the soil. Consequently, a standard shift in agronomic practices concerning rice straw management is warranted to enhance resource utilization efficiency and system productivity. Hence, the present study objects to explore diverse nitrogen dosages and scheduling regimes in wheat crop to achieve improved productivity, microbial dynamics and enzymatic activities in the North-western Indian Plains.